LAW ENFORCEMENT ACTIVITY: THEORETICAL ASPECT - Kunev, Yurii; Mazur, Anatolii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to analyze and reveal the problems of the theoretical and practical plan and prospects for the development of legal regulation of law enforcement activities based on the creation of its theoretical model. Research methods: a comprehensive approach to creating a theoretical picture of the object and applying the methodological scheme of “double knowledge” about the object as such and about the knowledge that describes and depicts it; comparative legal and doctrinal knowledge of administrative legislation, as well as a method of generalization and modeling of new theoretical knowledge of administrative law. Results: the problems of the further development of the theory and practice of public law are identified and a theoretical approach to their solution is proposed. It has been established that the system of law enforcement activity needs activity modeling, for the further creation of legal models of both law enforcement activity in general and its varieties. Such modeling of law enforcement activities can increase the effectiveness of implementation and protection of the rights and legitimate interests of Ukrainian citizens. In the absence of the integrity of such a system, there are gaps in the quality of legal support for the implementation of constitutional principles, embodied in the norms of public law – norms-standards for law enforcement activities. Discussion: the proposition is argued that the practical implementation of approaches based on the construction and implementation of a system of law enforcement activity models are effective for the practical implementation of the development needs of increasing the effectiveness of the implementation of the state’s security function.